Insights into the role of endolysosomal calcium signalling in epithelial-to-mesenchymal transition, autophagy and chemosensitivity of colorectal cancer / Aisyah Hasyila Jahidin ... [et al.] - Jahidin, Aisyah Hasyila; Hazizul Hasan, Mizaton; Abd Latip, Normala; Eshak, Zolkapli; Jamaludin, Siti Yusrina Nadihah (Faculty of Pharmacy, 2024)
Colorectal cancer (CRC) is a prevalent and deadly disease. In 2020, nearly 2 million cases were diagnosed globally, resulting in approximately 1 million fatalities annually [1]. The burden of CRC is projected to escalate to 3.2 million new cases and 1.6 million deaths by 2040. In Malaysia, CRC ranks as the second most common cancer and the third leading cause of cancer-related deaths [2]. The CRC treatment plan hinges on the tumour location and disease stage. Surgery is the primary approach, and radiotherapy or chemotherapy may be recommended to enhance prognosis. However, in metastatic CRC, chemotherapy often leads to drug resistance and disease progression. Two critical factors that contribute to this resistance are autophagy and epithelial-to-mesenchymal transition (EMT) [3].